Therapeutic Effect of Large Channel Endoscopic Decompression in Lumbar Spinal Stenosis - Wei, Fei-Long; Du, Ming-Rui; Li, Tian; Zhu, Kai-Long; Zhu, Yi-Li; Yan, Xiao-Dong; Yuan, Yi-Fang; Wu, Sheng-Da; An, Bo; Gao, Hao-Ran; Qian, Ji-Xian; Zhou, Cheng-Pei (Frontiers in Surgery, 2021)
Abstract Background: Percutaneous endoscopic decompression (PED) is a minimally invasive surgical technique that is now used for not only disc herniation but also lumbar spinal stenosis (LSS). However, few studies have reported endoscopic surgery for LSS. Therefore, we conducted this study to evaluate the outcomes and safety of large channel endoscopic decompression. Methods: Forty-one patients diagnosed with LSS who underwent PED surgery were included in the study. The estimated blood loss, operative time, length of hospital stay, hospital costs, reoperations, complications, visual analogue scale (VAS) score, Oswestry Disability Index (ODI) score, Japanese Orthopaedic Association (JOA) score and SF-36 physical-component summary scores were assessed. Preoperative and postoperative continuous data were compared through paired-samples t-tests. The significance level for all analyses was defined as p < 0.05. Results: A total of 41 consecutive patients underwent PED, including 21 (51.2%) males and 20 (48.8%) females. The VAS and ODI scores decreased from preoperatively to postoperatively, but the JOA and SF-36 physical component summary scores significantly increased. The VAS (lumbar) score decreased from 5.05 ± 2.33 to 0.45 ± 0.71 (P = 0.000); the VAS (leg) score decreased from 5.51 ± 2.82 to 0.53 ± 0.72 (P = 0.000); the ODI score decreased from 52.80 ± 20.41 to 4.84 ± 3.98 (P = 0.000), and the JOA score increased from 11.73 ± 4.99 to 25.32 ± 2.12 (P = 0.000). Only 1 patient experienced an intraoperative complication (2.4%; dural tear), and 1 patient required reoperation (2.4%). Conclusions: Surgical treatment for LSS is to sufficiently decompress and minimize the trauma and complications caused by surgery. This study did not reveal any obvious shortcomings of PED and suggested PED is a safe and effective treatment for LSS.